AYURVEDIC DRUGS IN PREVENTION AND MANAGEMENT OF AGE RELATED COGNITIVE DECLINE: A REVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Age related cognitive decline is a term reserved for abnormal cognitive function less severe than dementia in person older than 50. It is considered as a prior condition to senile dementia. The term dementia signifies cognitive deterioration so severe that social and occupational functioning of an individual is markedly impaired to such an extent that he can no longer remain a fully independent and productive citizen. As the disease progresses, the personality of an individual also changes and subsequently, social withdrawal take a hold. Advanced dementia is characterized by progressive loss of personality and increasing disability to perform even a simplest task. According to World Health Organization, it is estimated that 5% of men and 6% of women of above 60 years of age affected with Alzheimer’s type of dementia worldwide. According to Alzheimer’s Disease International there are 35.6 million people living with dementia worldwide in 2010, increasing to 65.7 million by 2030 and 115.4 million by 2050. Degeneration of the cerebral neurons is one of the commonest and important causes of dementia with advancing age which leads to deterioration of quality of life in elderly. Therefore it is of prime importance to curb this progress of cognitive decline before it crosses the threshold to dementia. Ayuveda is full of evidences regarding use of single drugs or formulations in age related cognitive decline. The drugs either mentioned as Medhya rasayanas specifically or other having Medhya activity can be potentially used for prevention and management of age related cognitive decline.